Neuroprotective Effects of Wharton Jelly Stem Cell-Derived Exosomes Developed as Nano-Drug Delivery System in 6-OHDA-Induced Neurotoxicity in 2D and 3D Neuronal Cell Line - Yavuz, Burcak; Yildiz, Asli Pinar Zorba; Abamor, Emrah Sefik; Darici, Hakan; Allahverdiyev, Adil M. (SPRINGER HEIDELBERG, 2024)
PurposeThe underlying mechanism of today's neurodegenerative diseases is disordered due to neuronal damage and very limited neuronal regeneration. Formulations that can be developed against the factors that cause damage must have a neuroprotective effect. Particularly, formulations that can be developed in nanoscales may play a key role in central nervous system diseases. This article aimed to investigate the neuroprotective activity of dopamine-loaded exosomes in which exosomes derived from Wharton jelly stem cells (WJ-MSCs) are used as carrier systems in 2D and 3D cell cultures induced in cell damage.Materials and MethodsThis study created 2D and 3D cell cultures with a bioprinter in the dopaminergic neuroblastoma cell line (SH-SY5Y). Cell lines were damaged with 6-OHDA. The neuroprotective effect of dopamine-loaded exosomes was investigated by Live&Dead analysis and immunostaining.ResultsThe findings showed that dopamine-loaded exosomes protected against 6-OHDA-induced neurotoxicity in both cultures. The increase in the number of viable cells in the 6-OHDA administered groups proved the neuroprotective effect.ConclusionWe predict that the carrier systems developed with exosomes obtained from Wharton jelly stem cells will be a light of hope in the treatment of neurodegenerative diseases, considering both their size and their contribution to regeneration.Lay SummaryEspecially in neurodegenerative diseases, it is very important to be able to protect and regenerate neurons. Wharton jelly stem cell-based exosomes are known to have many properties, including other wound healing activities. In addition, considering both the structure and size of exosomes, its development as a drug delivery system is promising.
Keywords: Regenerative medicine; Exosome; Wharton jelly stem cell; Drug delivery system; 3D cell culture; Neuroprotective effects; PARKINSONS-DISEASE; IN-VITRO; BRAIN; MECHANISMS; VESICLES; THERAPY; TUBULIN; Engineering